The regional effect of the consumer directed care model for older people in Australia - Tran, My (Michelle); Gannon, Brenda (My University, 2021)
Evaluation of Consumer Directed Care (CDC), an internationally recognized means to promote autonomy and choices in the delivery of health in community aged care, is growing, but little is known about the spatial implications of such policy. With differences in the utilisation of home care services across locations, the introduction of a national CDC program may affect different regions to different extents. This paper explores the regional effect of the CDC introduction on older Australians' mental health. We analyse data on 1780 individuals aged 65 years and over, from 11 waves (2007-2017) of the Household, Income and Labour Dynamics in Australia (HILDA) Survey. We find that older adults' mental health is worse after the introduction of the CDC in 2013. Moreover, older adults, who lived in the areas with higher utilisation of Home Care Packages, experienced worse mental stress than the same individuals who lived in the areas with lower utilisation of home care services. This pattern may reflect regional differences in Government funding, community aged care waiting time and provider service fees. Therefore, it is important for health policies that aim to promote choices to older consumers, such as CDC, to consider regional differences in its implementation, to minimise unwarranted variations in the population health and well-being.
Social Science and Medicine
Keywords: Consumer directed care; Difference-in-difference; HILDA; Ageing; Health and wellbeing